(untitled) (Altre Modernità, 2015)
The book is an object which can be considered as a window in the novel Die unendliche Geschichte (1979) written by Michael Ende. It allows Bastian to look at the world of Phantasien and to communicate indirectly with the Childlike Empress. Furthermore, this object will show its function as an symbol of evolution, which will enable the passage of the protagonist into the world of Phantasien: first the book appears as a window, then it becomes a two-way-mirror that allows Bastian and Atreju to look at each other, and finally it turns into a gate which enables them to live many adventures together. Die unendliche Geschichte can be considered as a modern Bildungsroman in which the young protagonist gradually reaches his maturation. This progress must be seen in a psychological perspective: it is the growth of a child-mind through literature which makes reference to the German novel tradition but also (as children’s literature) to the world of unconsciousness.